2021
DOI: 10.3390/molecules26206218
|View full text |Cite
|
Sign up to set email alerts
|

Polarisation of Electron Density and Electronic Effects: Revisiting the Carbon–Halogen Bonds

Abstract: Electronic effects (inductive and mesomeric) are of fundamental importance to understand the reactivity and selectivity of a molecule. In this article, polarisation temperature is used as a principal index to describe how electronic effects propagate in halogeno-alkanes and halogeno-alkenes. It is found that as chain length increases, polarisation temperature decreases. As expected, polarisation is much larger for alkenes than for alkanes. Finally, the polarisation mode of the carbon–fluorine bond is found to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Therefore, using the external electrostatic potential as a probe and the polarization energy, entropy, and density as electronic responses, one can get qualitative and quantitative insight into the reactivity and the selectivity of molecular fragments. 483 (3.9.5) Fuentealba : One should not forget that, along with density functionals, one has density functions as a special case. Ramon Carbó-Dorca Carre has studied the mathematical structure of such functions.…”
Section: What Is the Status Of Dft-based Tools For Interpretationmentioning
confidence: 99%
See 4 more Smart Citations
“…Therefore, using the external electrostatic potential as a probe and the polarization energy, entropy, and density as electronic responses, one can get qualitative and quantitative insight into the reactivity and the selectivity of molecular fragments. 483 (3.9.5) Fuentealba : One should not forget that, along with density functionals, one has density functions as a special case. Ramon Carbó-Dorca Carre has studied the mathematical structure of such functions.…”
Section: What Is the Status Of Dft-based Tools For Interpretationmentioning
confidence: 99%
“…where r k 0 (r) is the transition density coupling the kth state to the ground state. 483 From a link between conceptual DFT and statistical thermodynamics, it has been shown that the perturbation energy due to intermolecular electrostatic interactions can be understood in terms of effective work and heat exchange, 484 the first-order correction Ð r r ð Þdv r ð Þdr being the effective work and the secondorder correction in eqn (60) being the heat exchange. A polarization entropy and a polarization temperature can also been defined by this analogy.…”
Section: Pccp Perspectivementioning
confidence: 99%
See 3 more Smart Citations